Epidermal skin grafting. (September 2016) - Herskovitz, Ingrid; Hughes, Olivia B; Macquhae, Flor; Rakosi, Adele; Kirsner, Robert
Abstract: Autologous skin grafts, such as full‐ and split‐thickness, have long been part of the reconstructive ladder as an option to close skin defects. Although they are effective in providing coverage, they require the need for a trained surgeon, use of anaesthesia and operating room and creation of a wound at the donor site. These drawbacks can be overcome with the use of epidermal skin grafts (ESGs), which can be harvested without the use of anaesthesia in an office setting and with minimal to no scarring at the donor site. ESGs consist only of the epidermal layer and have emerged as an appealing alternative to other autologous grafts for the treatment of acute and chronic wounds. In this article, we provide an overview of epidermal grafting and its role in wound management.